New taxa of southern African Sesiini (Lepidoptera: Sesiidae) - Bartsch, Daniel (Zootaxa, 2015)
Two new genera of Sesiini from southern Africa, each comprising only a single species are described and figured: Microsesia nana, new gen., new sp. (holotype in TMPS) and Coccophila, new gen., with Coccophila pythes (Druce, 1899), new comb. (holotype in BMNH). Bionomical data for Coccophila pythes are given for the first time.